Spatial modelling of papaya dieback disease occurrence - Nurul Hawani Idris; Marliana Azman; Sazlieya Saupi Teri; Erneeza Mohd Hata; Mohamad Hafis Izran Ishak (Penerbit Universiti Kebangsaan Malaysia, 2023)
The incident of papaya dieback disease has resulted in huge losses due to the decrement in crop yield. The disease is affecting papaya production in Malaysia, putting papaya production at risk, primarily to accommodate the national and export trading needs. Abiotic factors have been identified as agents influencing the occurrence of papaya disease, however, little study includes the possible influence of landscape features on disease occurrence. Therefore, using a spatial model, this study aims to investigate the influence of weather variables and the surrounding landscape on papaya dieback disease in Batu Pahat district, Johor, Malaysia. This study applied an Ordinary Least Square (OLS) regression to identify the dominant abiotic factors influencing the papaya disease incident. The main finding revealed that the distance of disease incidents significantly influences the rate of papaya dieback disease based on the affected points (crop) to the nearby road; the percentage area of papaya dieback disease incidence was negatively related to the distance from the road. In other words, being closer to road features may increase the size of the affected area. This research could benefit stakeholders in strategising agricultural practices including planning suitable landscape and topographic characteristics of newly planted areas to reduce the occurrence of such disease.